2012
DOI: 10.5489/cuaj.65
|View full text |Cite
|
Sign up to set email alerts
|

Current status of cytokine therapy in management of patients with metastatic renal cell carcinoma

Abstract: Studies examining the efficacy of immunotherapy have used a variety of end points such as response rate (RR), complete response (CR) or partial response (PR); rate of progression; and progression-free and median survival. However, these studies used different definitions of these end points and none was blinded.5 Further, RR has been reported to be an unreliable surrogate of survival. 5A meta-analysis 7 of 1042 patients found that the overall proportion of responses (CR and PR) to interferon-α was 12%. CRs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…15,16 Newer targeted therapies like temsirolimus, sunitinib, and sorafenib have shown improved HRQoL compared with interferon-α. However, no direct comparisons between these agents have been reported that show an improvement in HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Newer targeted therapies like temsirolimus, sunitinib, and sorafenib have shown improved HRQoL compared with interferon-α. However, no direct comparisons between these agents have been reported that show an improvement in HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…These agents are associated with low response rates (<15%) and significant toxicities, which often limit their use and affect patient quality of life (QoL) [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Cytokine therapy with interleukin-2 (IL-2) or interferon-alpha (IFN-α) had been the standard approach to treating mRCC patients for over 20 years. However, poor response rates, marginal survival benefit and significant toxicity [3] prompted the development of alternative treatment options for the majority of patients. As the understanding of the molecular biology underlying RCC has increased, specific molecular targets have been identified for potential therapies.…”
Section: Introductionmentioning
confidence: 99%